Adaptive Ɩ0-LMS based algorithm for solution of power quality problems in PV-STATCOM based system - Nimita A. Gajjar; Tejas Zaveri; Naimish Zaveri (Institute of Advanced Engineering and Science, 2023)
This paper presents grid tied PV-STATCOM system using an adaptive Ɩ0-LMS based control algorithm. The proposed Ɩ0-LMS with adaptive zero attractor is used for single stage grid connected PV-STATCOM system and it highlights the performance of system for maintaining unity power factor, reducing harmonics and zero voltage regulation with nonlinear and unbalanced load. In this the Ɩ0norm constraint LMS algorithm, the optimal value of zero attractor is time varying instead of a fixed value such that it gives better results with variable input systems such as PV power. The system is tested on a low cost prototype developed using STM32F407VG microcontroller and the results are found satisfactory.